The art of invention : the creative process of discovery and design - Paley, Steven J., 1955- (Amherst, N.Y. : Prometheus Books, 2010)
The lowly paperclip attracts little attention in our world of advanced gadgets and increasingly sophisticated technology. But to veteran inventor and design engineer Steven J. Paley, it is a prime example of the qualities that often characterize a great invention--simplicity, elegance, and robustness--and it provided a lasting solution to a common problem. Paley shows why these same three qualities are essential not only to the success of simple devices, but equally to complex inventions from computer chips to nuclear power plants.--From publisher description
PART I. THE PROCESS OF INVENTION -- Chapter 1. The Paper Clip and the Problem -- What Makes a Great Idea Great? -- The History of the Paper Clip -- What's the Problem? -- Is It the Right Problem? -- Reframing the Problem -- The Evolving Invention -- Invention in Context -- Chapter 2. The Hidden Obvious -- The Destination -- Being Confidently Naive -- The Vision and the Visionary -- Needfinding and Paradigms -- Seeing the Hidden Obvious -- The Vision Refined -- Chapter 3. Creativity and the Brain -- The Creative Mind -- Feeding the Brain -- Listening to Your Subconscious -- Thinking with the Gut -- Your Inner Senses -- Working Ideas, Percolation, and Not Falling in Love -- Action versus Thought: The Importance of Doing -- Chapter 4. The Process of Invention -- The Flash of Inspiration -- The Resonance of an Idea -- Sources of Innovation -- Applications of Life Experience -- Making the Familiar New -- Applying Physical Principles -- Accidental and Chance Observations -- Learning from Nature -- The Processes of Invention -- PART II. DESIGN AND INVENTION -- Chapter 5. Simplicity -- Profound Simplicity -- The Simple and the Complex -- Zero Mass Design -- Chapter 6. Elegance -- The Many Facets of Elegance -- Ingenious Simplicity: The Most from the Least -- Core Inventions: From Screws to Microprocessors -- Adaptive Inventions: The Elegance of Self-Regulation -- Smart Inventions: Inventions That Change with Change -- Characteristics of Elegance -- A Summary -- Chapter 7. Robustness -- Strength -- Redundancy -- Simplicity -- Self-Healing -- Managed Failure -- PART III. MAKING IT HAPPEN -- Chapter 8. Problem Solving and Iteration -- A Systems Approach: Connect the Big Pieces First -- KISS: Keep It Simple, Stupid -- Testing, Testing, 1, 2, 3 -- What You Couldn't See from There, You Can See from Here -- Attacking from the Bottom -- Inventing while You Sleep -- Arbitrate and Iterate -- Limiting the Scope -- Stopping -- Putting It All Together -- Anticipating the Unanticipated -- Documentation -- Summary -- Chapter 9. The Business of Invention -- Inventing as an Employee -- Selling Your Inventions -- Entrepreneurship: Starting Your Own Company -- Patents -- The Business of Invention -- Chapter 10. The Art of Invention -- The Unexplored: Hard Work, Fear, and Fantasy -- Experience and Invention -- The Art of Getting It Wrong -- The Hidden Obvious Revisited -- Serendipity -- The Staircase of Creativity -- The Pleasure of the Problem -- The Inventor's Tool Kit -- Making It Real -- The Art and the Science -- The Future Is Yours to Create.
Includes bibliographical references (p. 215-219) and index.
Keywords: Engineering; Inventions